The Dynamics of Unlikely Slip: 3D Modeling of Low‐Angle Normal Fault Rupture at the Mai'iu Fault, Papua New Guinea. (25th May 2022) - Biemiller, J.; Gabriel, A.‐A.; Ulrich, T.
Abstract: Despite decades‐long debate over the mechanics of low‐angle normal faults (LANFs) dipping less than 30°, many questions about their strength, stress, and slip remain unresolved. Recent geologic and geophysical observations have confirmed that gently dipping detachment faults can slip at such shallow dips and host moderate‐to‐large earthquakes. Here, we analyze the first 3D dynamic rupture models to assess how different stress and strength conditions affect rupture characteristics of LANF earthquakes. We model observationally constrained spontaneous rupture under different loading conditions on the active Mai'iu fault in Papua New Guinea, which dips 16°–24° at the surface and accommodates ∼8 mm/yr of horizontal extension. We analyze four distinct fault‐local stress scenarios: (1) Andersonian extension, as inferred in the hanging wall; (2) back‐rotated principal stresses inferred paleopiezometrically from the exhumed footwall; (3) favorably rotated principal stresses well‐aligned for low‐angle normal‐sense slip; and (4) Andersonian extension derived from depth‐variable static fault friction decreasing toward the surface. Our modeling suggests that subcritically stressed detachment faults can host moderate earthquakes within purely Andersonian stress fields. Near‐surface rupture is impeded by free‐surface stress interactions and dynamic effects of the gently dipping geometry and frictionally stable gouges of the shallowest portion of the fault. Although favorably inclined principal stresses have been proposed for some detachments, these conditions are not necessary for seismic slip on these faults. Our results demonstrate how integrated geophysical and geologic observations can constrain dynamic rupture model parameters to develop realistic rupture scenarios of active faults that may pose significant seismic and tsunami hazards to nearby communities. Plain Language Summary: Movement across faults allow parts of the Earth's crust to move past each other in response to forces driven by tectonic plate motions and can occur during large, devastating earthquakes. The orientation of a fault relative to the direction of the forces and stresses loading determines how easily it can "slip" in any given direction and whether it will continue to slip or if new fractures and faults will form instead. Some faults appear to be geometrically misoriented and thus "locked" relative to their local forces, but nonetheless continue to move on the scale of mm per year and accommodate crustal motions. Here, we develop data‐constrained computer models to test how different forces at depth affect the movement and associated potential earthquake magnitude of one of these misoriented faults: the Mai'iu normal fault in Papua New Guinea. Our results suggest these faults can indeed slip in large earthquakes under tectonic crustal stress conditions, and that locally favorably rotated stresses would generate even larger earthquakes. We find that seismic slip does not always reach the Earth's surface and explore various physical mechanisms limiting near‐surface slip on these faults. Key Points: We perform the first 3D dynamic rupture simulations of low‐angle normal fault (LANF) earthquake scenarios constrained by laboratory and field evidence Large LANF earthquakes are dynamically viable under various stress conditions including perfectly Andersonian extension Shallow slip is limited by the stabilizing effects of shallow fault geometry, velocity‐strengthening gouges, and free‐surface interactions